The effect of sociocultural identities on study destination choice - Hendriana, Evelyn; Awang, Khairil Wahidin; Raja Yusof, Raja Nerina; Bojei, Jamil (Universiti Putra Malaysia Press, 2020)
There are very few studies that consider the relationship between sociocultural identities and tourists’ destination choices, in which almost none focusing on the education tourism context. The objective of this research was to examine the effect of national identity, consumer cosmopolitanism and consumer ethnocentrism on international study destination choice. One hundred and twenty questionnaires were distributed to final year high school students, with a usable response rate of 75.83%. The data were analysed using partial least square-structural equation modelling (PLS-SEM). The study found a significant positive effect of consumer cosmopolitanism on students’ intention to study in Australia based on their perceived image of the destination and institutions. Contrary to the proposed hypothesis, national identity had a significant positive effect on the destination image of Australia.